Zasada prawdy materialnej w świetle projektowanej nowelizacji Kodeksu postępowania cywilnego - Kamieński, Grzegorz (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2019)
The principle of truth is one of the basic principles of civil proceedings. The article discusses changes in the provision of art. 3 of the k.p.c. in the planned amendment of the CCP. The author presents the view that changes in the CCP will result in the principle of substantive truth in the CCP.
Keywords: principle of truth; principle of substantive truth; Code of Civil Procedure